Database security, volume X status and prospects : IFIP TC11/WG 11.3 Tenth International Conference on Database Security, 22-24 July 1996, Como, Italy - Samarati, Pierangela; Sandhu, R. (Ravinderpal) (Chapman & Hall on behalf of the International Federation for Information Processing, 1997)
The purpose of this book is to discuss, in depth, the current state of research and practice in database security, to enable readers to expand their knowledge. The book brings together contributions from experts in the field throughout the world. Database security is still a key topic in mist businesses and in the public sector, having implications for the whole of society.